SOLVING THE LABORATORY DILEMMA IN DISTANCE LEARNING GENERAL CHEMISTRY - Reeves, Jimmy; Kimbrough, Doris (Online Learning, 2004)
Making a laboratory science course accessible to distance learners requires eliminating certain barriers. This paper describes one semester introductory chemistry courses for science and non-science majors that feature laboratory experiments that students can do at home, using materials readily available from local grocery and hardware stores. Courses using this approach have been offered successfully for several years at the University of Colorado at Denver, Cape Fear Community College and the University of North Carolina at Wilmington, and the laboratory experiences of the distance learners compares favorably with that of traditional students. This paper describes the important features of the distance learning courses, and provides assessment results that indicate the suitability of these experiments as replacement for traditional laboratories.